Regional myocardial dysfunction assessed by two-dimensional speckle tracking echocardiography in systemic sclerosis patients with fragmented QRS complexes - ÇİNÇİN, AHMET ALTUĞ; ÖZBEN SADIÇ, BESTE; ATAŞ, HALİL; SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT; DİRESKENELİ, RAFİ HANER (CHURCHILL LIVINGSTONE INC MEDICAL PUBLISHERS, 2014)
Background: The aim of the study was to explore the relation between regional myocardial dysfunction and fragmented QRS (fQRS) complexes in systemic sclerosis (SSc). Methods: Fifty-three SSc patients and 26 controls were included. All subjects underwent speckle tracking echocardiography for evaluation of left ventricular (LV) function and ECG to check for fQRS complexes. Results: SSc patients had significantly lower LV global longitudinal, radial and circumferential strain and twist compared to controls. Thirteen SSc patients had fQRS (DII, DIII, aVF leads in eleven patients and V1 to V5 leads in two patients) and they had significantly lower global longitudinal and circumferencial strain compared to SSc patients with normal QRS. The SSc patients with fQRS in DII, DIII, and aVF leads had impaired longitudinal strain and delay in time to peak longitudinal strain in inferior LV segments compared to those with normal QRS. Conclusion: fQRS is associated with lower strain measures in SSc patients indicating impairment in LV function. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Fragmented QRS; Speckle tracking echocardiography; Systemic sclerosis; DILATED CARDIOMYOPATHY PATIENTS; GLOBAL LONGITUDINAL STRAIN; CORONARY-ARTERY-DISEASE; CARDIAC INVOLVEMENT; VENTRICULAR DYSSYNCHRONY; NONINVASIVE ASSESSMENT; DIFFUSE SCLERODERMA; RADIAL STRAIN; ABNORMALITIES; INTERVAL